Math, asked by dwijendranathray16, 11 months ago

Prove:-
Tan 6° tan 42° tan 66° tan78°=1

Answers

Answered by rajeevr06
2

Answer:

We know that

 \tan( \alpha )  \tan(60 -  \alpha ) \tan(60 +  \alpha )   =  \tan(3 \alpha )

now LHS

 \tan(6)  \tan(60 - 6)  \tan(60 + 6) \tan(42)   \tan(78)  \times  \frac{1}{ \tan(54) }  =

  \frac{ \tan(3 \times 6)  \tan(42)  \tan(78) }{ \tan(54) }  =  \frac{ \tan(18) \tan(60 - 18) \tan(60 + 18)   }{ \tan(54) }  =  \frac{ \tan(3 \times 18) }{ \tan(54) }  = 1 \: proved

Similar questions